An English vocabulary learning app with self-regulated learning mechanism to improve learning performance and motivation. Issue 3 (4th March 2019) - Chen, Chih-Ming; Chen, Liang-Chun; Yang, Shun-Min
Abstract: In recent years, numerous English vocabulary learning-assisted apps have been developed to enlarge learners' English vocabulary through mobile learning. However, the ability of learners to engage in self-regulated learning (SRL) importantly affects performance in autonomously learning English vocabulary using mobile apps. Therefore, this study developed an English vocabulary learning app with a self-regulated learning mechanism (EVLAPP-SRLM) to help learners improve their SRL abilities, with a view to improving their learning performance and motivation in a mobile learning context. To evaluate the performance of the proposed EVLAPP-SRLM, a total of 46 Grade 5 students were recruited from two classes in an elementary school of Taoyuan City, Taiwan, to participate in the experiment. The two classes were randomly assigned to the experimental or control groups, which used, respectively, the EVLAPP-SRLM and the English vocabulary learning app without a self-regulated learning mechanism (EVLAPP-NSRLM) to support their English vocabulary learning during a period of two weeks. Experimental results indicate that the learners in the experimental group exhibited significantly better learning performance and motivation than those in the control group. Moreover, the learners who used EVLAPP-SRLM exhibited significantly greater learning performance and motivation than those who used EVLAPP-NSRLM, regardless of gender. Analytical results also verify that the EVLAPP-SRLM provides more benefits to field-dependent learners than to field-independent learners with respect to learning performance and motivation.